Recovering co-created service failures: the missing link of perceived justice and ethicalness. Issue 7 (25th November 2019) - Wei, Shuqin; Ang, Tyson; Anaza, Nwamaka A.
Abstract : Purpose: Drawing on the fairness theory, this paper aims to propose a conceptual framework that investigates how co-creation in the failed service delivery (coproduction intensity) and co-creation in the service recovery affect customers' evaluation of the firm's competence, justice and ethicalness, and ultimately their willingness to co-create in the future. Design/methodology/approach: Tax services were chosen as the research context. A consumer panel consisting of individuals who live in the USA and have used tax preparation services within the past year was recruited. The first study explores what happens to customers' ethical perceptions during a failed co-created service encounter. A secondary study investigates what happens to customers' ethical perceptions in the event that the failed co-created service is recovered. Findings: The findings show that customers' perceptions of the firm's abilities and ethics are impeded by coproduction intensity but favorably influenced by co-creation of recovery. Practical implications: A sense of ethicalness and fairness is violated when co-created service failure occurs, but fortunately, practitioners can count on engaging customers in the service recovery process as co-creators of the solution to positively alter perceived ethicalness and fairness. Originality/value: Failed co-created services represent an under-researched area in the marketing literature. Current investigations of co-created service failures have largely approached the notion of fairness from a perceived justice perspective without referencing ethical judgments. However, fairness is grounded in basic ethical assumptions of normative treatment. This research is among the first to highlight the importance of perceived ethicalness in the context of co-created service failure and recovery.